2015
DOI: 10.1016/j.jneuroling.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in grammatical processing strategies for active and passive sentences: An fMRI study

Abstract: a b s t r a c tMany studies have used a neuroscience-based approach towards examination of writing and reading skills and how these might differ between languages. However, few studies have focused on differences in grammatical processing that may be specific to certain languages. Studies have shown that grammar for active and passive sentences differs between Chinese and English. Chinese, a morphologically non-inflectional language, is visibly different from inflectional languages in terms of verb morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…When reading passive sentences, this initial thematic role assignment is incorrect and has to be revised. This reanalysis process has been proposed as an explanation for greater left IFG activation for passive sentences (Feng et al, 2015;Mack, Meltzer-Asscher, Barbieri, & Thompson, 2013). In our study, we observed decoding in a posterior portion of left IFG (pars opericularis; BA44), which may reflect these processes of reanalysis.…”
Section: Discussionsupporting
confidence: 64%
“…When reading passive sentences, this initial thematic role assignment is incorrect and has to be revised. This reanalysis process has been proposed as an explanation for greater left IFG activation for passive sentences (Feng et al, 2015;Mack, Meltzer-Asscher, Barbieri, & Thompson, 2013). In our study, we observed decoding in a posterior portion of left IFG (pars opericularis; BA44), which may reflect these processes of reanalysis.…”
Section: Discussionsupporting
confidence: 64%
“…This interpretation is further supported by an Italian study that demonstrated improved accuracy on the comprehension of passive sentences after transcranial magnetic stimulation in the left posterior parietal cortex (Finocchiaro et al, 2015). NP-movement was also associated with the left pars triangularis of the IFG for both Japanese (Yokoyama et al, 2006; Hirotani et al, 2011) and Chinese passives (Ye and Zhou, 2009), and the left pars orbitalis of the IFG in Chinese passives (Feng et al, 2015). In contrast, a few studies comparing passives to actives reported activation only in non-traditional language areas such as the left frontal operculum, caudal to the IFG (Yokoyama et al, 2007), and the postcentral gyrus (Matchin and Hickok, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with several Japanese and Chinese NP-movement studies that also compared passive and active structures. However, it should be noted that unlike Japanese and English passives which are marked by an additional morpheme in the verb, the Chinese language has no morphological inflections (Yokoyama et al, 2007; Feng et al, 2015). Temporoparietal activity was reported in the left posterior superior temporal gyrus (STGp) (Kinno et al, 2008; Hirotani et al, 2011) for Japanese and Chinese passives, and the left superior parietal lobule (Yokoyama et al, 2006) and left inferior parietal lobule (IPL) (Yokoyama et al, 2007) for Japanese passives only–areas which have all been previously implicated in thematic re-analysis and verb-argument integration (Thompson and Meltzer-Asscher, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Because left IFG revealed stronger activation for processing complex syntax even in a non-word detection task, the authors claimed task-independent involvement of this region in syntactic processing. Similarly, an FMRI study in Chinese also reported stronger activation in left IFG and posterior superior temporal gyrus for processing passive sentences compared to active sentences [ 51 ]. Because passive sentences are assumed by generative-transformational theories to be more complex than active sentences [ 52 ], the authors associated left IFG with syntactic movement processing in Chinese as in other Indo-European languages.…”
Section: Discussionmentioning
confidence: 98%